Gastrodin Mitigates Ketamine-Induced Inhibition of F-Actin Remodeling and Cell Migration by Regulating the Rho Signaling Pathway - Ping-Cheng Shih; I-Shiang Tzeng; Yi-Chyan Chen; Mao-Liang Chen (Biomedicines)
Background/Objects: Rho signaling plays a role in calcium-regulated cytoskeletal reorganization and cell movement, processes linked to neuronal function and cancer metastasis. Gastrodia elata, a traditional herbal medicine, can regulate glutamate-induced calcium influx in PC12 cells and influence cell function by modulating neuronal cytoskeleton remodeling via the monoaminergic system and Rho signaling. This study investigates the effects of gastrodin, a key component of Gastrodia elata, on Rho signaling, cytoskeleton remodeling, and cell migration in B35 and C6 cells. It also explores gastrodin’s impact on Rho signaling in the prefrontal cortex of Sprague Dawley rats. Methods: B35 cells, C6 cells, and Sprague Dawley rats were treated with ketamine, gastrodin, or both. The expression of examined proteins from B35 cells, C6 cells, and the prefrontal cortex of Sprague Dawley rats were analyzed using immunoblotting. Immunofluorescent staining was applied to detect the phosphorylation of RhoGDI1. F-actin was stained using phalloidin-488 staining. Cell migration was analyzed using the Transwell and wound-healing assays. Results: Gastrodin reversed the ketamine-induced regulation of cell mobility inhibition, F-actin condensation, and Rho signaling modulation including Rho GDP dissociation inhibitor 1 (RhoGDI1); the Rho family protein (Ras homolog family member A (RhoA); cell division control protein 42 homolog (CDC42); Ras-related C3 botulinum toxin substrate 1(Rac1)); rho-associated, coiled-coil-containing protein kinase 1 (ROCK1); neural Wiskott–Aldrich syndrome protein (NWASP); myosin light chain 2 (MLC2); profilin1 (PFN1); and cofilin-1 (CFL1) in B35 and C6 cells. Similar modulations on Rho signaling were also observed in the prefrontal cortex of rats. Conclusions: Our findings show that gastrodin counteracts ketamine-induced disruptions in Rho signaling, cytoskeletal dynamics, and cell migration by regulating key components like RhoGDI1, ROCK1, MLC2, PFN1, and CFL1. This suggests the potential of gastrodin as a comprehensive regulator of cellular signaling.